Improving Student Learning Outcomes through the Snowball Throwing Model in General Administration Learning Class X OTKP1 SMK Negeri 2 Palu - Burhanudin Santabang (Pinisi Business Administration Review, 2021)
Snowball Throwing is one of the new learning methods and one of the effective learning models applied in schools, where this model can train and motivate students in participating in the teaching and learning process in the classroom. The location of this classroom action research is at SMK Negeri 2 Palu, which is located at Jalan Setia Budi No. 58 Palu, Central Sulawesi. The research subjects were 33 students of class X OTKP1 consisting of 6 boys and 27 girls. The design of this research is classroom action research (CAR). This study uses 2 cycles and each cycle consists of 4 stages, namely Planning, Implementation, Observation, and Reflection. There are two types of research data, namely qualitative data collected by using the Observation sheet, namely conducting a series of direct observations of the research and quantitative data collected after giving a test at the end of each cycle. The data analysis techniques carried out are data reduction, presenting data, and drawing conclusions/verification. The results of the research conducted indicate that the application of the Snowball Throwing model can improve student learning outcomes in the subjects of General Administration in class X OTKP1 SMKN 2 Palu.